Short report: Comparison of performance of serum and plasma in panbio dengue and Japanese encephalitis virus enzyme-linked immunosorbent assays - Stuart D. Blacksell (2018)
We examined the comparative performance of serum and plasma (in dipotassium EDTA) in Panbio Dengue enzyme-linked immunosorbent assays (ELISAs) for detection of non-structural protein 1 (NS1), IgM, and IgG, and a dengue/Japanese encephalitis virus (JEV) combination IgM ELISA in a prospective series of 201 patients with suspected dengue in Laos. Paired comparisons of medians from serum and plasma samples were not significantly different for Dengue IgM, and NS1 which had the highest number of discordant pairs (both 2%; P = 0.13 and P = 0.25, respectively). Comparison of qualitative final diagnostic interpretations for serum and plasma samples were not significantly different: only 1.5% (3 of 201 for Dengue/JEV IgM and Dengue IgG) and 2.0% (4 of 201; IgM and NS1) showed discordant pairs. These results demonstrate that plasma containing EDTA is suitable for use in these ELISAs. Copyright © 2012 by The American Society of Tropical Medicine and Hygiene.